2017
DOI: 10.1074/jbc.m117.793034
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of Cdr1 kinase localization and phosphorylation during osmotic stress

Abstract: Environmental conditions modulate cell cycle progression in many cell types. A key component of the eukaryotic cell cycle is the protein kinase Wee1, which inhibits the cyclin-dependent kinase Cdk1 in yeast through human cells. In the fission yeast , the protein kinase Cdr1 is a mitotic inducer that promotes mitotic entry by phosphorylating and inhibiting Wee1. Cdr1 and Wee1 both localize to punctate structures, termed nodes, on the medial cortex, but it has been unknown whether node localization can be altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(48 reference statements)
0
9
0
2
Order By: Relevance
“…These nodes have been proposed as an important element in cell size control, as their number scales with cell size, and cdr2 mutants defective in node association are defective in size control [ 3 , 18 ]. Recent studies have suggested that the Cdr1 and Cdr2 kinases in the nodes transiently recruit and inactivate Wee1 by phosphorylation [ 19 , 20 ]. Upstream Cdr2 regulators include an inhibitory kinase Pom1 [ 21 , 22 ] and an activating kinase CaMK Ssp1 [ 4 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…These nodes have been proposed as an important element in cell size control, as their number scales with cell size, and cdr2 mutants defective in node association are defective in size control [ 3 , 18 ]. Recent studies have suggested that the Cdr1 and Cdr2 kinases in the nodes transiently recruit and inactivate Wee1 by phosphorylation [ 19 , 20 ]. Upstream Cdr2 regulators include an inhibitory kinase Pom1 [ 21 , 22 ] and an activating kinase CaMK Ssp1 [ 4 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…This prevents Swe1 degradation, leading a transient G2 arrest and, thus, a delay in progression into M phase, thereby allowing adaptation to osmostress. It should be noted that the same mechanism has been proposed in Schizosaccharomyces pombe [60], together with alternative mechanisms where the SAPK sty1 regulates cdc25, the phosphatase involved in inhibiting the mitosis repressor wee1 [61]. Similar to the fission yeast, activated p38 is required for a G2/M checkpoint involving Cdc25B and Cdc25C, which regulate the activity of the CDK-cyclin B1 complex during mitosis.…”
Section: Regulation Of G1 S and G2 Phases By Sapks Upon Stressmentioning
confidence: 70%
“…These nodes are formed by Cdr2 oligomers that are required for Cdr1 and Wee1 recruitment (Martin and Berthelot-Grosjean, 2009;Moseley et al, 2009;Allard et al, 2018). We previously identified a mutant cdr1(∆460-482) that fails to localize to nodes and results in elongated cell size at division like cdr1∆ ( Fig 5A) (Opalko and Moseley, 2017). We tested the effects of artificially recruiting mEGFP-cdr1(∆460-482) back to nodes using cdr2-GBP-mCherry, which contains the GFP-binding peptide (GBP).…”
Section: Spatial Control Of Cdr1-wee1 Signaling In Cellsmentioning
confidence: 99%
“…Cells were then lysed in 100µl sample buffer (65mM Tris pH 6.8, 3% SDS, 10% glycerol, 10% 2-mercaptoethanol, 50mM sodium fluoride, 50mM β-gylcerophosphate, 1mM sodium orthovanadate, complete EDTA-free protease inhibitor tablet (Pierce)) in a Mini-beadbeater-16 for 2 minutes. Blots were probed with anti-FLAG M2 (Sigma), anti-GST (Covance), anti-Cdr1 (Opalko and Moseley, 2017), anti-Wee1 (Allard et al, 2018), anti-cdc2 (Santa Cruz Biotechnologies sc-53217), anti-pY15 (Cell Signaling #9111L), anti-His (Santa Cruz Biotechnologies sc-8036), and anti-thiophosphate ester (Abcam ab92570).…”
Section: In Vitro Kinase Assay and Western Blotsmentioning
confidence: 99%